Material study and conservation of face-mounted photographs and digital prints - Mireya Arenas; Silvia Garcia Fernandez-Villa (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Face-mounting of photographs is a method of exhibiting contemporary photography which is widespread nowadays in museums and galleries, and which presents specific problems in the field of conservation and restoration. The research presented here includes the study of its main constituent materials, considers different types of sources and documentation, and also addresses analysis and accelerated aging tests which are currently being developed.